Subject to change: the lessons of Latin American women's "testimonio" for truth, fiction, and theory - Bartow, Joanna R. (North Carolina studies in the Romance languages and literatures, 2018)
Cover -- Title -- Copyright -- CONTENTS -- ACKNOWLEDGMENTS -- INTRODUCTION -- CHAPTER 1: LEGITIMATION: MEDIATED TESTIMONIOS, AUTHORITY AND VICARIOUS IDENTITIES -- CHAPTER 2: FICTIONS OF TESTIMONY: ESSENTIALIZED IDENTITIES AND THE OTHER IN ONESELF IN TWO WORKS BY CLARICE LISPECTOR -- CHAPTER 3: READING TESTIMONIO WITH THEORY: VIOLENCE, SACRIFICE, DISPLACEMENT -- CHAPTER 4: BEYOND TESTIMONIO IN TWO WORKS BY DIAMELA ELTIT -- CONCLUSION -- WORKS CITED -- INDEX -- Back Cover